The Dual Impact of Trade Wars on Emerging Market Economies: A Study on the Link between Economic Growth Volatility and Global Influence - Song, Chuhan (International Journal of Social Sciences and Public Administration, 2025)
This study examines the impact of the US–China trade war on emerging market economies (EMEs), with a specific focus on how it has exacerbated economic growth volatility and shaped strategic positioning. Using a mixed-methods approach, we construct two composite indices-the Economic Volatility Index and the Global Influence Index-via principal component analysis (PCA), drawing on data from five representative EMEs (Brazil, India, South Africa, Turkey, and Vietnam) between 2013 and 2021. We identify a moderate negative correlation between global influence and economic volatility at the aggregate level, yet country-level analysis unveils substantial heterogeneity: nations with greater influence exhibited milder volatility, whereas less influential economies experienced intensified instability. After the trade war, driven by national heterogeneity, the divergence trend among different countries has become further pronounced. These findings underscore the dual role of the trade war as both an economic disruptor and a strategic catalyst, highlighting how domestic policies and economic structures mediate its effects. This study offers novel insights into the resilience and adaptive strategies of EMEs in an era of great-power competition.